Economic effects of the East-West Highway - Tasana Patanapanich; Prof. John Hugh Jones; Prof. Utai Voodhigula; Dr. Chai Muktabhant; Dean Milton E. Bender Jr. (Bangkok : SEATO Graduate School of Engineering, 1964)
The objective of this study has been to investigate the role of the East-West Highway in the economic development of the region through which it is located. A study of the traffic on the East-West Highway was made to explore the traffic pattern as an aid to understanding the usage of the highway. Direct benefits, gained by the users of the highway, are described. Agricultural economic development, one of the more important phases studied, is concerned with production of vegetables, upland crops, paddy, and poultry. An investigation of forest product output was made for the following commodities: teak and non-teak timber, fuel wood, and charcoal. Social development, concerned primarily with business and commercial activity and the value of road side land, was also studied. Time-series changes in agricultural production, forest production, and business activity in the East-West Highway area were compared to data for other areas having similar environmental conditions. The two datum regions selected, Sukhothai-Tak and Tak-Kampangpetch provinces, have transportation facilities roughly comparable to those existing in the study region prior to construction of the East-West Highway. Conclusions have been drawn pertaining to the economic effects of the East-West Highway.
Thesis (M.Eng.) - SEATO Graduate School of Engineering
A thesis submitted in partial fulfillment if the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Keywords: Highway research -- Economic aspects